Peran Keterangan Ahli Bagi Hakim dalam Memutus Perkara Tindak Pidana Lingkungan Hidup (Studi Putusan Nomor 71/PID.B/LH/2021/PN SNT) - Adri, Saidil; Putra, Rahmat Angga Dwi (Wajah Hukum, 2026)
Environmental crimes differ from general crimes because the object of evidence involves technical and scientific elements. Evidence is a crucial aspect of the trial process, as it is through this stage that a defendant's guilt or innocence is determined. In environmental cases, expert testimony is crucial as a bridge between the scientific and legal worlds. This study aims to analyze the role of expert testimony for judges in deciding environmental crime case No. 71/Pid.B/LH/2021/PN Snt. This research is normative research with a statutory, case study, and conceptual approach. The results indicate that, in handling environmental cases, an expert is held to a higher standard, given the central role of expert testimony in translating scientific findings into legal evidence. Although expert opinions are independent, judges are not bound to use them as the basis for their decisions; rather, the panel of judges follows the expert's opinion as a consideration in their decisions.